Genetic Polymorphism of Angiotensin-Converting Enzyme and Chronic Obstructive Pulmonary Disease Risk: An Updated Meta-Analysis. (18th October 2016) - Kang, Sang Wook; Kim, Su Kang; Chung, Joo-Ho; Jung, Hee-Jae; Kim, Kwan-Il; Kim, Jinju; Ban, Ju Yeon
Abstract : The relationship between polymorphism of the angiotensin I converting enzyme ( ACE ) gene and chronic obstructive pulmonary disease (COPD) has been examined in many previous studies. However, their results were controversial. Therefore, we performed a meta-analysis to evaluate the relationship between the ACE gene and the risk of COPD. Fourteen case-control studies were included in this meta-analysis. The pooled p value, odds ratio (OR), and 95% confidence interval (95% CI) were used to investigate the strength of the association. The meta-analysis was performed using comprehensive meta-analysis software. Our meta-analysis results revealed that ACE polymorphisms were not related to the risk of COPD (p > 0.05 in each model). In further analyses based on ethnicity, we observed an association between insertion/deletion polymorphism of the ACE gene and risk of COPD in the Asian population (codominant 2, OR = 3.126, 95% CI = 1.919–5.093, p < 0.001 ; recessive, OR = 3.326, 95% CI = 2.190–5.050, p < 0.001 ) but not in the Caucasian population (p > 0.05 in each model). In conclusion, the present meta-analysis indicated that the insertion/deletion polymorphism of the ACE gene may be associated with susceptibility to COPD in the Asian population but not in the Caucasian population. However, the results of the present meta-analysis need to be confirmed in a larger sample.